Affordable housing public private partnership : a case study of international housing solutions - Kutama, Neo (My University, 2017)
In the context of declining government funding for affordable housing in South Africa, relying solely on government subsidies to deliver housing for low income households is unsustainable. Public private partnerships (PPPs) have to therefore be considered as one of the possible alternative solutions to address the shortage that exists within this sector. The objective of the study was to determine the suitability of PPP to improve the delivery of affordable housing within the South African context. This was answered in a case study approach by exploring a private equity investing organisation which contributes significantly within affordable housing space, International Housing Solutions (IHS). The case study also provides some insights into their successful business model. The findings of the study revealed that PPP is a suitable model to improve the quality of affordable housing in South Africa. The study also highlighted conditions that must be met to achieve quality affordable housing in South Africa through PPPs. The research concludes by making recommendations to both the government and the public sector in light of the findings of this research. Limitations for the study were highlighted and other variables to be researched that are important to further understanding of PPP as a model to improve the delivery of affordable housing in South Africa were suggested.
A research report submitted to the Faculty of Engineering and the Built Environment, University of Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Building, October 2017
Keywords: Public-private sector cooperation--South Africa; Public contracts--South Africa